2018
DOI: 10.5007/2175-8042.2018v30n53p152
|View full text |Cite
|
Sign up to set email alerts
|

Motivação de crianças e adolescentes praticantes de esportes em projetos de inclusão social do Rio de Janeiro

Abstract: O objetivo desta pesquisa visa analisar o efeito do clima motivacional e comportamental criado pelos professores de um projeto de inclusão social (PIS) por meio do esporte sobre a orientação de vida de seus alunos. Para esta análise foi utilizado o TEOSq aplicado em 42 jovens de ambos os sexos, na faixa etária de 10 a 17 anos, que participam dos PIS oferecidos pela Secretaria de Esporte e Lazer de São João de Meriti e sua Vila Olímpica, nas modalidades de dança, futebol, jiu-jítsu e vôlei. Estes 42 foram class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 7 publications
0
5
0
11
Order By: Relevance
“…In Barreto and Perfeito's (2018) research, the results indicated that social inclusion projects through sport do not appear to influence individuals in the value construction, such as preventing adherence to crime that they are exposed. However, the results of the present survey indicate that adolescents participating of educational sports programs reveal information that favors the deconstruction of homogeneous sports, and through subjective values in sportive practice of educational character, the subjects manifest positive values transferable to other instances of life.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In Barreto and Perfeito's (2018) research, the results indicated that social inclusion projects through sport do not appear to influence individuals in the value construction, such as preventing adherence to crime that they are exposed. However, the results of the present survey indicate that adolescents participating of educational sports programs reveal information that favors the deconstruction of homogeneous sports, and through subjective values in sportive practice of educational character, the subjects manifest positive values transferable to other instances of life.…”
Section: Resultsmentioning
confidence: 93%
“…The manner that the sport sets on people's life nowadays is object of investigation of several studies (BARBOSA and ARAÚJO, 2015;BARRETO and PERFEITO, 2018;BELTRAME et al, 2015;BENELI, PRONI, MONTAGNER, 2016;FREITAS and STIGGER, 2016). The educational sport is not just the practiced on the school, but a much bigger proposal that the school sport, since this action strives to reproduce positive values capable of conduct people to replicate a "high performance" for life, experiencing the diferente abilities of the other, considernig the specificities of the movement of each one and, above all, living and respecting everyone's inabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Já Barreto (1987) interpreta que realmente existe uma falta de prática associativa do cidadão brasileiro e justifica a questão contextualizando-a historicamente, apontando para que o fato decorre da própria história do Brasil. Como colônia de Portugal, desde o início da colonização a coroa portuguesa evitava a todo custo a convivência associativa entre nativos e também entre os imigrantes aqui deportados.…”
Section: Associações Voluntáriasunclassified
“…Vale dizer, que o descompasso entre os interesses do grupo e os interesses de quem esta na representação ou no comando de uma associação é um fator determinante para o fracasso da mesma. Neste sentido, podemos citar Barreto (1987) que expõe alguns fatores intervenientes para o sucesso das associações. São eles: a) As iniciativas não podem ser frutos de idéias isoladas, sem um consenso ou envolvimento dos demais associados.…”
Section: Características Do Associativismounclassified
See 1 more Smart Citation